2016
DOI: 10.18632/oncotarget.13916
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of IFNγ-producing natural killer cells induced by cytomegalovirus reactivation after haploidentical hematopoietic stem cell transplantation

Abstract: During human cytomegalovirus (CMV) infection after umbilical cord blood or HLA-matched hematopoietic stem cell transplantation (HSCT), a population of NKG2C-expressing natural killer (NK) cells expand and persist. The expanded NK cells express high levels of inhibitory killer immunoglobulin-like receptors (KIR) specific for self-HLA and potently produce IFNγ. However, it remains unknown whether similar events would occur after haploidentical HSCT (haplo-HSCT). Here, we demonstrated that IFNγ-producing NK cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 40 publications
0
25
0
1
Order By: Relevance
“…Knowing that a low IFN-γ response to phytohemagglutinin (PHA) predicts poor survival [11], I assessed CMV-specific and mitogen-induced IFN-γ release using the same commercial quantiferon-cytomegalovirus assay. Unfortunately, in the quantiferon technique, the interferon immune response after CMV-peptide-laden human leukocyte antigen (HLA) class I stimulation showed higher level than PHA-induced in the first wave of lymphocyte reconstitution (i.e., between 2–11 and 19–01), which of note, was during most intensive CMV reactivation [12].…”
Section: Resultsmentioning
confidence: 99%
“…Knowing that a low IFN-γ response to phytohemagglutinin (PHA) predicts poor survival [11], I assessed CMV-specific and mitogen-induced IFN-γ release using the same commercial quantiferon-cytomegalovirus assay. Unfortunately, in the quantiferon technique, the interferon immune response after CMV-peptide-laden human leukocyte antigen (HLA) class I stimulation showed higher level than PHA-induced in the first wave of lymphocyte reconstitution (i.e., between 2–11 and 19–01), which of note, was during most intensive CMV reactivation [12].…”
Section: Resultsmentioning
confidence: 99%
“…This CMV-induced memory-like NK-cell population is characterized by low expressionof CD56, expression of CD57, lack of the inhibitory NKG2a receptor, and expression of the activating heterodimeric receptor CD94-NKG2C ( 20 , 21 ). The memory-associated features of these CMV-induced NK include secondary expansion and enhanced capacity to produce IFN-γ upon CMV reactivation ( 20 , 22 , 23 ). Once induced, their expansion is not limited to CMV reactivation, as stimulation via the low affinity Fc receptor IIIa (CD16) by IgG, as well as pro-inflammatory cytokines, can contribute to the expansion, persistence, and functional properties of CMV-induced memory-like NK cells ( 21 , 24 , 25 ).…”
Section: Possible Mechanisms Of Anti-leukemic Effects Of CMV After Almentioning
confidence: 99%
“…Alternatively, in partially HLA-mismatched HSCT, the anti-leukemic effect may be related to the general mechanism of NK-cell self-tolerance, which is mediated by inhibitory receptors, such as killer cell immunoglobulin-like receptors (KIR), that recognize self-MHC class I molecules. According to the “missing-self hypothesis,” recipient AML cells can be the target for cytotoxicity of donor-derived NKG2C + NK cells, induced upon CMV infection, as they lack donor HLA molecules ( 23 ).…”
Section: Possible Mechanisms Of Anti-leukemic Effects Of CMV After Almentioning
confidence: 99%
“…Additional studies are needed to clarify if these instances of NKG2C + NK expansion in the absence of acute HCMV are due to cross-reactive antigens (either viral or viral-induced host) between CMV and these other infections, to the specific inflammatory milieu elicited, to (subclinical) CMV reactivation, or to some combination of these factors. Several studies have suggested that CMV reactivation and the subsequent expansion of NKG2C + NK cells may improve clinical outcomes for leukemia patients [7780], and a recent study found that among CMV-seropositive patients newly infected with HIV, a higher frequency of NKG2C + CD57 + NK cells correlated with lower HIV viral load and more rapidly reaching undetectable viremia levels after combination antiretroviral therapy [81]. It will be of great interest to determine what clinical benefits there may be to patients that experience an expansion of the NKG2C + NK cell population in the setting of antiviral immunity against additional infections.…”
Section: Antigen-dependent Generation Of Nk Cell Memorymentioning
confidence: 99%